Effect of tillage, weed-control practices and nitrogen fertilization on performance of rice (Oryza sativa) under intermediate deep-water condition - SHARMA, A R (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1990 and 1991 at Cuttack to study the effect of tillage practices (autumn, summer and pre-monsoon ploughings) along with weed-control methods [manual. chemical and post-establishment inter-crop cultivation (beushen)] and N levels (0-60 kg N/ha) on direct-sown 'Gayatri' rice (Oryza sativa L.) under intermediate deep-water condition (0-50 cm). In 1991 the grain yield of rice increased significantly with frequency of ploughing. but in 1990 (when weed infestation was less) the yield was more with 2 ploughings [summer (March) and pre-monsoon (May)] than with 3, ploughings [autumn (January), March and May] or 1 ploughing (just before sowing in May). Hand-weeding at 10 and 40 days after germination, early application of butachlor @ 2 kg/ha followed by hand-weeding at 40 days and inter-crop cultivation (beushen) provided equally gOod weed control and increased the yield up to 15.5% in 1990 and 25.9% in 1991 compared with the unweeded control. The effect of weed-control measures wasmore pronounced with less number of ploughings. particularly in 1991 dueto higher weed biomass. further, in 1991 (When crop-weed competition was allowed unchecked) N application increased the yield up to 20 kg/ha under 3 ploughings but not under 2 ploughings. Moreover. the grain yield decreased linearly with N application under I ploughing due to considerable increase in dry weight of weeds. Therefore off-seasontillage particularly in summer along with mechanical or chemical weed control was found essential for improving the N-use efficiency and productivity of rain fed lowland rice.